Intellectual Stimulation of Women's Transformational Leadership in Improving Institutional Brand Image - Maunah, Binti; Safi’I, Asrop; Yuhana, Nihayatul Laili (Yayasan Indonesia Emerging Literacy Education, 2024)
Education is one of the efforts to improve human quality. One of the elements that makes education more qualified, Various problems that are inseparable from life as an organization. These problems cover several aspects, such as defining goals, determining policies, developing programs, employing people, providing facilities, achieving results and coordinating separate activities. All of these activities require the involvement of people with different ability backgrounds, such as professional supervisors, and other personnel. This study aims to describe: Intellectual stimulation of women's transformational leadership in improving institutional brand image at the Bahrul Ulum Mambaiyyah Islamic Boarding School (BUM) in South Lampung Regency. This study uses a qualitative approach. This type of research can be used to find and understand what is hidden behind a phenomenon that is sometimes difficult to know or understand. Data collection in this study uses in-depth interview techniques, observation, and documentation where the data sources are from people, documents (paper) and places (place). While to obtain data obtained from informants in various forms such as written notes, interviews, observations and photos. Both from leaders, staff, stakeholders and also those involved in the management of the Bahrul Ulum Mambaiyyah Islamic Boarding School (BUM) in South Lampung Regency. The results of this study can be concluded that; In intellectual stimulation, Mbah Nyai is seen from her intelligence, tenacity, relationships, willingness to sacrifice and uniqueness in her preaching. As well as the charismatic and revolutionary leadership model approach and policies based on the mandate of the vision, mission and objectives of the institution and the mandate.